Hubungan Strategi Coping dengan Kecemasan saat Presentasi pada Mahasiswa Angkatan 2024 di Program Studi Diploma Tiga Keperawatan Universitas Abulyatama - Widya Asmaliza; Urip Pratama; Ellyza Fazlylawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The students often faced experiences that cause anxiety in the early semester of the college period, especially in the presentation session. To overcome this, students need strong coping strategies. Coping strategies help people deal with stress. We interviewed 12 students from the 2024 batch at Abulyatama University's Nursing Program on October 29, 2024. Most of them (10 out of 12) said they often feel anxious and nervous when presenting or speaking in front of many people, which makes them less focused. This study aims to explore the correlation of coping strategies with anxiety during presentation among college students. This study uses a descriptive analytical design with a cross-sectional approach. The sample was 189 Diploma III nursing students 2024,the study took from march 21st to may 1st,2025 and chosen using a total sampling technique. The questionnaire, Brief Cope, and PSAS with Cronbach's Alpha were employed in this study. The result indicated 0.6 for coping strategies and PSAS Cronbach Alpha = 0.90. Univariate and bivariate analysis using the chi-square test was used to analyze the data. The finding reveals that the coping strategies were Public Speaking Anxiety, which is the medium category, with as many as 87 respondents (58.8). Based on the result of the chi-square test, the ρ-value is 0.000 (< 0.05). The findings indicate a correlation between coping strategies and anxiety during presentation among students. This study is expected to provide valuable insights and knowledge for educators and mentors on the benefits of Coping Strategies in enhancing public speaking confidence and improving teaching quality.